The effects of waste urea formaldehyde powder on mechanical and morphological properties of polypropylene - (:unkn) unknown (Metal Powder Industries Federation, 2017)
The importance of alloys and blends has increased gradually in the polymer industry so that the plastics industry has moved toward complex systems. The main reasons for making polymer blends are the strengthening and the economic aspects of the resultant product. In this study, polypropylene matrix contributes to ground urea formaldehyde powder is handled as 0, 5, 10 and 20 % ratio will be mixed in the extruder. Mixture obtained from the extruder to be granulated and then the granules will be obtained as appropriate standard test sample of the injection molding machine. Mechanical and morphological tests will be applied such as elasticity modulus, yield strength, ultimate tensile strength, % elongation, Izod impact strength, hardness, density. Also, SEM examination will be conducted to evaluate the microstructure of urea formaldehyde particles as well as material distribution in these experiments. © 2017 Metal Powder Industries Federation. All Rights Reserved.